Cytoskeleton in the Parasitic Plant Cuscuta During Germination and Prehaustorium Formation - Kaštier, Peter; Krasylenko, Yuliya A.; Martinčová, Michaela; Panteris, Emmanuel; Šamaj, Jozef; Blehová, Alžbeta (Frontiers in Plant Science, 2018)
Although cytoskeleton is a driving force for cell division and growth in higher plants, there is little evidence about its components in parasitic angiosperms. Microtubules and actin filaments in cells of shoot apical meristem and root-like structure of stem holoparasites European (C. europaea L.) and Eastern (C. monogyna Vahl.) dodders, as well as in prehaustorium, the specific organ adapted to parasitism, were visualized for the first time by immunolabeling and fluorescence microscopy. The significance of cytoskeletal elements during germination and prehaustorium formation was addressed by treatments with taxol, oryzalin, latrunculin B, cytochalasin B/D, jasplakinolide, and 2,3-butanedione monoxime. In shoot apical meristem many dividing cells were observed, in contrast to root-like structure, devoid of cell divisions. Cortical microtubules were oriented transversely and/or obliquely, while actin filaments were randomly distributed in cells of both organs. Furthermore, longitudinal cortical microtubules were present in digitate cells of prehaustorium, and transverse arrays were found in its file cells. Long and short random actin filaments were also observed in prehaustorium cells. Thus, it was shown that the cytoskeleton in dodder shoot cells is organized in a similar way to non-parasitic dicots, while cytoskeletal organization has some peculiarities in quickly senescing root-like structure and prehaustorium.